The Intersection of the Green and the Smart City: A Data Platform for Health and Well-Being through Nature-Based Solutions - Dionysia Kolokotsa; Aikaterini Lilli; Elisavet Tsekeri; Kostas Gobakis; Minas Katsiokalis; Aikaterini Mania; Neil Baldacchino; Sevasti Polychronaki; Niall Buckley; Daniel Micallef; Kurt Calleja; Emma Clarke; et al. (Smart Cities, 2023)
An increasingly important aspect of analyzing the challenges facing cities today is the integration of nature. Nature-based solutions have the potential to successfully cope with the adverse effects of extensive urbanization and climatic change. On the other hand, the incorporation of smartness in cities is a critical issue. This paper aims to analyze the steps towards integrating nature-based solutions and smart city aspects to develop a web-based data platform that focuses on tackling and investigating the role of nature-based solutions in city health and well-being and returns a digital twin of the natural and built environment, including health-related key performance indicators. Seven pilot cities are used as a basis for the analysis. The architecture of a smart green city data platform is described. The interaction with the citizens is ensured through apps and games. The paper lays the foundation for a future “phygital” NBS world.